THE ZEIGARNIK EFFECT - Kontinou, Rafaela; Georgiou, Dimitra; Giamarellos, Pavlos; Bitha, Malena (Open Schools Journal for Open Science, 2025)
The Zeigarnik Effect describes our tendency to remember uncompleted or interrupted tasks more than completed ones. Named after psychologist Bluma Zeigarnik, this phenomenon has profound implications in learning, productivity, and even personal relationships. This paper explores the origin of the effect, its psychological foundation, experimental backing, and its relevance in everyday applications from goal-setting to improving memory and emotional wellbeing.